Effectiveness Of The Pediatric Assessment Triangle (PAT) For Emergency Department Care: Literature Review - Yayang - Harigustian; Alfi - Syahri; Sriyono - -; Hakim - Zulkarnain (Universitas Tribhuwana Tunggadewi, 2025)
Inappropriate use of triage can lead to negative impacts, one of which is the delay in diagnosis and appropriate treatment for pediatric patients who need immediate attention, which can increase the risk of complications and morbidity in pediatric patients. Pediatric-specific triage instruments are needed because there are significant differences in clinical conditions, disease responses, and treatment needs between pediatric and adult patients. Children have different physiological, anatomical, and psychological characteristics compared to adults. The purpose of this study was to determine the effectiveness of the Pediatric Assessment Triangle for care in the emergency department. The method used in this study is to use a literature review approach. The literature review search was conducted on 6 databases namely PubMed, Science Direct, Google Scholar, Scopus, Web of Science Scopus, and Cinahl using the keyword â€œPediatric Assessment Triangleâ€. Based on the search results, 924 articles were found and after filtering only 6 articles were used. The results showed that the Pediatric Assessment Triangle was effectively used to triage children in the emergency department. The conclusion of this study is that training or socialization about PAT is needed to increase knowledge and empower health workers involved in implementing the Pediatric Assessment Triangle (PAT).